Dispute Resolution on Muḍārabah Musytarakah Contract on Sharia Insurance in Indonesia: Between Regulation and Practice - Riska Fauziah Hayati; Abdul Mujib (Institut Agama Islam Negeri Palangka Raya, 2022)
This paper discussed on how to resolve disputes over the muḍārabah musytarakah contract in sharia insurance by looking at the applicable sharia insurance dispute settlement regulations and sharia insurance policies. This research was normative legal research using the documentation method. The results showed that in various regulations and policies regarding sharia insurance, there are various alternatives (choice of forum) in dispute resolution, including in the muḍārabah musytarakah contract. In general, sharia economic dispute resolution can be done in two ways, namely litigation and non-litigation. Litigation dispute resolution was guided by the mandate of Law Number 3 of 2006 on Religious Courts. Several alternative non-litigation dispute resolutions are mentioned in various regulations, including: by deliberation and consensus; through mediation institutions that are independent and impartial; through an association by the business activities of a sharia insurance company; or the Shari'ah Arbitration Board. Then, in the sharia insurance general policy, there are also various alternative dispute resolutions, including amicably reaching a mutual agreement. But if it is not successful, then the dispute resolution will be carried out through the Indonesian Insurance Mediation Board (BMAI); through the Sharia Arbitration Board; Religious Courts/District Courts in the policy area are issued, or the participant chooses one of the dispute resolution options and is obliged to notify the company.